Laser Powder Bed Fusion – Materials Issues and Optimized Processing Parameters for Tool steels, AlSiMg‐ and CuCrZr‐Alloys1 . Issue 4 (23rd February 2017) - Buchmayr, Bruno; Panzl, Gerhard; Walzl, Alexander; Wallis, Christopher
Abstract : Laser Powder Bed Fusion (L‐PBF) is the main technology for additive manufacturing of metallic components and is primarily used for rapid prototyping and tooling in cases with very complex geometry or lightweight design and small quantities. There are manifold influencing parameters, which need to be optimized in order to build components with suitable properties. The paper deals with three distinct application fields, like the development of new tool steel grades for injection molds, light weight design using aluminum alloys with optimized post‐weld heat treatment as well as production of copper alloys without porosity. The most sensitive process parameters are displayed and the multi‐layered components are characterized using light and high‐resolution microscopy as well as mechanical testing. Abstract : The Laser Powder Bed Fusion (L‐PBF) process is suitable to process ferrous and non‐ferrous materials. The work describes the usability of two new steel grades for L‐PBF process, the influence of post‐weld heat treatments on the AlSi10Mg alloy, including microstructure, as well as mechanical properties and the investigations on CuCrZr parts, discussing mechanical, and thermal properties after heat treatment.